Self-Efficacy Dan Digital Vision Dalam Cloud Accounting Adoption Terhadap MSME Sustainability Performance - Khadik, Muhammad Vikrul; Purwantini, Anissa Hakim; Farida, Farida (SUSTAINABLE, 2025)
This study examines digital vision and computer self-efficacy (CSE) as antecedents of cloud accounting adoption and investigates how that adoption, in turn, affects digital transformation and sustainability performance among micro, small, and medium-sized enterprises (MSMEs) in Magelang Regency and Magelang City, Indonesia. Using a quantitative design, survey data were collected from 146 MSMEs had implemented cloud technologies in their operations. Partial Least Squares–Structural Equation Modeling (PLS-SEM) was employed to test the hypothesized relationships. The results indicate that digital vision and CSE have a significant positive effect on the adoption of cloud accounting. Furthermore, the adoption of cloud accounting has been proven to significantly drive the digital transformation of SMEs, which ultimately contributes positively to improving sustainability performance, both economic, social, and environmental aspects. These findings underscore the importance of strengthening CSE and cultivating a clear digital vision among MSME owners and managers to enhance technology adoption and sustain competitive advantage. Policy-wise, government-backed training in CSE and targeted digital mentoring emerge as pivotal levers for accelerating digital transformation and achieving triple bottom line–based sustainability outcomes.